Simulation of plastic injection of molding electrical appliances [electronic resource] - Nadiah Rahmat, 1986- (2009)
Project Paper (Sarjana Kejuruteraan (Mekanikal - Pembuatan)) - Universiti Teknologi Malaysia, 2009